Racial/Ethnic Differences in Sex Hormone Levels among Postmenopausal Women in the Diabetes Prevention Program - Kim, Catherine (Endocrine Society, 2012)
CONTEXT: Sex hormones may differ by race/ethnicity in postmenopausal women. Whether racial/ethnic differences also exist among those who are overweight and glucose intolerant is not clear. OBJECTIVES: The objective of the study was to compare sex hormones by race/ethnicity [non-Hispanic white (NHW), Hispanic, African-American (AA)] in overweight, glucose-intolerant, postmenopausal women. DESIGN: This was a secondary analysis of a randomized controlled trial. PARTICIPANTS: Participants included postmenopausal glucose-intolerant women participating in the Diabetes Prevention Program. INTERVENTIONS: Interventions included intensive lifestyle modification (consisting of diet and physical activity) or metformin 850 mg twice a day vs. placebo. MAIN OUTCOME MEASURES: Baseline levels and 1-yr intervention-related changes in SHBG, total and bioavailable estradiol (E2), total and bioavailable testosterone, and dehydroepiandrosterone were measured. RESULTS: At baseline, among women not using estrogen (n = 370), NHW had higher total and bioavailable E2 and testosterone levels than Hispanics independent of age, type of menopause, waist circumference, alcohol intake, and current smoking. NHW also had higher levels of bioavailable E2 and lower levels of SHBG than AA. At baseline, among estrogen users (n = 310), NHW had higher total and bioavailable E2 than Hispanics and higher levels of SHBG than AA after adjustment. At 1 yr, among women not using estrogen, NHW had larger declines in total E2 and bioavailable E2 levels than AA after adjustment for the above covariates, changes in waist circumference, and randomization arm. At 1 yr, among estrogen users, sex hormone changes did not differ by race/ethnicity. CONCLUSIONS: Among postmenopausal women, there were significant race/ethnicity differences in baseline sex hormones and changes in sex hormones.